Distinct Age-Specific Effects on Olfactory Associative Learning in C57BL/6 Substrains - Chen, Hung-Lun; Chen, Chien-Fu F.; Huang, Han-Bin (Frontiers in Behavioral Neuroscience, 2022)
C57BL/6 is the most widely used mouse strain in the laboratories. Two substrains of C57BL/6, C57BL/6J (B6J), and C57BL/6N (B6N) are well-known backgrounds for genetic modification and have been shown difference in quite a few tests, including open field test, rotarod test, and Morris water maze. However, difference between these two substrains in olfaction-dependent behaviors remains unknown. Here, we used olfactory two-alternative choice task, which is modified to have two training stages, to evaluate animals’ ability in instrumental learning and olfactory association. In the first (rule learning) stage, the mice were trained to use the operant chamber to collect water rewards. An odor cue was provided in the procedure, with no indication about reward locations. In the following (discrimination learning) stage, two odor cues were provided, with each indicating a specific water port. The animals were rewarded upon correct port choices following cue deliveries. We found that during young adulthood (7–10 weeks old), proportionally more B6J than B6N mice were able to pass rule learning (58.3% vs. 29.2%) and ultimately acquire this task (54.2% vs. 25%), with the two substrains showing similar pass rates in discrimination learning (92.9% vs. 85.7%). Surprisingly, at a more mature age (17 weeks old), this substrain difference disappeared. Mature B6N mice had a significant improvement in pass percentages of rule learning and overall task, whereas similar improvement was not observed in the B6J counterparts. Instead, mature B6J mice had an improved speed in rule learning and overall task. We further examined behavioral patterns of 8-week-old B6J and B6N mice in the olfactory habituation or dishabituation test. We observed normal olfactory habituation from subjects of both substrains, with the B6J mice exhibiting stronger investigative responses to newly presented odorants. These results reveal for the first time that B6J and B6N mice are different in acquisition processes of a behavioral task that requires instrumental learning and olfactory association, and that maturation appears to employ different effects on these two substrains during these processes. Furthermore, young adult B6J and B6N mice might be similar in olfactory habituation but different in the olfactory aspects of novelty seeking.